2020
DOI: 10.1111/j.1936-704x.2020.03330.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Uranium and Arsenic in Unregulated Groundwater Sources – Western Navajo Nation

Abstract: Concentrations of dissolved uranium (U) and arsenic (As) above drinking water standards in unregulated water sources pose various human health risks. Although high natural background concentrations may occur in some environments (Runnells et al. 1992), anthropogenic contamination concerns are especially troublesome on the Navajo Nation (NN), where past U mining activity may have contaminated water supplies. This research investigated U and As groundwater contamination issues in unregulated wells in the western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Similarly, Jones et al. ( 2020 ) demonstrated the negative environmental impacts and human health risks associated with mining activities on unregulated groundwater sources in the Western Navajo Nation. While these case studies were conducted across different regions, all of them identified that populations exposed to high concentrations of chronic chemical contaminants (e.g., arsenic, uranium etc.)…”
Section: Drinking Water and Chronic Chemical Exposurementioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, Jones et al. ( 2020 ) demonstrated the negative environmental impacts and human health risks associated with mining activities on unregulated groundwater sources in the Western Navajo Nation. While these case studies were conducted across different regions, all of them identified that populations exposed to high concentrations of chronic chemical contaminants (e.g., arsenic, uranium etc.)…”
Section: Drinking Water and Chronic Chemical Exposurementioning
confidence: 94%
“…For instance, Ward et al (2018) did a meta-analysis of epidemiological studies and found linkages between an increased exposure to nitrates through drinking water and methemoglobinemia, adverse reproductive outcomes, cancer, and thyroid disease in women. Similarly, Jones et al (2020) demonstrated the negative environmental impacts and human health risks associated with mining activities on unregulated groundwater sources in the Western Navajo Nation. While these case studies were conducted across different regions, all of them identified that populations exposed to high concentrations of chronic chemical contaminants (e.g., arsenic, uranium etc.)…”
mentioning
confidence: 97%
“…7 These values are well below the threshold recommended by the World Health Organization. Yet there are eventually large deviations in uranium concentrations in drinking water 8 and these values need to be carefully monitored.…”
Section: Introductionmentioning
confidence: 99%
“…Surface water is scarce on the Colorado Plateau, and elevated uranium (U) in groundwater further complicates water access. Water scarcity is driven by a low annual rainfall that is below 20-30 cm per year (Credo et al, 2019;Jones et al, 2020;Ingram et al, 2020), and enrichments of U in these waters pose health concerns for people and animals (USDHHS 2013;Hund et al, 2015;Rock et al, 2019;Hoover et al, 2020;Ingram et al, 2020;Lister et al, 2021;Nozadi et al, 2022). The southern Colorado Plateau is the ancestral land of the Navajo (Diné) people and the current boundaries of the Navajo Nation are located entirely in the region (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%